A review on the occurrence of antibiotic-resistant bacteria found in abattoir effluent from resource-limited settings: The necessity of a robust One Health framework - Claudious Gufe; Tawanda Ashley Chari; Prosper Jambwa; Lawrance Dinginya; Precious Mahlangu; Sheunesu Theo Marowero; Chenai Sipiwe Majuru; Tafadzwa Kadungure; Jairus Machakwa (Sustainable Environment)
Abattoirs discharge untreated waste into surrounding bodies of water and the environment, which is extremely harmful to public health. Bacteria that cause disease, especially those resistant to antibiotics, may be present in these wastes. This review was carried out to provide a comprehensive overview of antibiotic-resistant microbes discovered in slaughterhouse wastes in resource-limited settings. Relevant research studies focussing on bacteria isolated from abattoir effluents in resource-limited settings and AMR patterns were searched on Google Scholar, PubMed, Web of Science, and African journals online. The studies showed that numerous bacteria were detected, such as Salmonella spp. Bacillus spp. Shigella spp. Escherichia coli, Pseudomonas aeruginosa, Citrobacter freundii, Proteus spp. Streptococcus spp. Yersinia spp. and Staphylococcus aureus. Several of these isolates were resistant to multiple antibiotics, including Penicillin, Vancomycin, Clindamycin, Erythromycin, Tetracycline, Ampicillin, Linezolid, Gentamycin, Ciprofloxacin, Ampicillin, Ceftriaxone, Imipenem, Cefotaxime, Chloramphenicol, Trimethoprim-sulfamethoxazole, Piperacillin-Tazobactam, Ceftazidime, Imipenem, and Meropenem. Lack of proper waste management practices due to financial constraints is the major cause of a high prevalence of resistant bacterial strains in abattoir effluents in resource-limited settings. Given the critical role that the environment plays in the spread and maintenance of antibiotic-resistant microorganisms, public health systems must strengthen One Health National Action plans applicable to abattoir effluents to successfully combat antibiotic resistance.